Correlations between Local Institutional Capacity and Community Conservation Partnerships in Lore Lindu National Park - Massiri, Sudirman Daeng; Hamzari; Pribadi, Hendra; Golar; Hamka; Akhbar; Naharuddin (Media Konservasi, 2024)
The Community Conservation Partnership (CCP) is a policy option for ensuring the sustainability of conservation functions while improving the local community's economy. The critical issue in implementing this policy is local institutional capacity. This study aimed to describe the correlation between local institutional capacity and the performance of community conservation partnerships in LLNP. This study was carried out in 10 villages that had established conservation partnership agreements with LLNP managers. This research adopted a quantitative descriptive method. This study revealed that CCP performance was significantly dependent on local institutional capacity. The CCP programme improved the function of conservation areas, but did not boost the local economy significantly. Trust and financial capacity are the essential organisational and management capacities that strongly correlate with CCP performance. The performance of CCP was more strongly correlated with the organisational and management capacity of the local institution than with individual capacity. The individual capacity of the local institution that strongly correlated with CCP performance was only the technical capacity in forestry. Therefore, strengthening capacity at organizational and management levels, such as building trust, communications, and funding support for local institutions, is crucial for improving and sustaining conservation partnerships.